2018
DOI: 10.1002/btpr.2655
|View full text |Cite
|
Sign up to set email alerts
|

Antibody expression stability in CHO clonally derived cell lines and their subclones: Role of methylation in phenotypic and epigenetic heterogeneity

Abstract: Routine CHO cell line development practices involve a lengthy process of iteratively screening clonally derived cell lines to identify a single line suitable for IND filing and clinical manufacture. Paramount in this process is development of a stable production cell line having consistent growth, productivity and product quality for the entire generational length of the manufacturing process. Scale-down stability models used to screen clones for consistency are time consuming and often a rate-limiting step in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…However, population heterogeneities can significantly affect the bioprocess performance, e.g., with differences in the intraclonal protein expression or metabolically different cell populations [4][5][6][7][8]. It was shown that even in monoclonal CHO cell lines ( [9], recently discussed in [10]), population heterogeneities with different phenotypes can spontaneously evolve [4,[11][12][13], and that cell-cycle-dependent population dynamics with variable productivities and metabolic regulations can be present in cell culture processes [14][15][16][17]. The formation and dynamics of physically-derived process heterogeneities are studied intensively in bioprocesses, e.g., evaluating spatial gradients of gas bubbles [18], concentration gradients of substrates [19] and oxygen [20], and pH gradients [21].…”
Section: Introductionmentioning
confidence: 99%
“…However, population heterogeneities can significantly affect the bioprocess performance, e.g., with differences in the intraclonal protein expression or metabolically different cell populations [4][5][6][7][8]. It was shown that even in monoclonal CHO cell lines ( [9], recently discussed in [10]), population heterogeneities with different phenotypes can spontaneously evolve [4,[11][12][13], and that cell-cycle-dependent population dynamics with variable productivities and metabolic regulations can be present in cell culture processes [14][15][16][17]. The formation and dynamics of physically-derived process heterogeneities are studied intensively in bioprocesses, e.g., evaluating spatial gradients of gas bubbles [18], concentration gradients of substrates [19] and oxygen [20], and pH gradients [21].…”
Section: Introductionmentioning
confidence: 99%
“…Single cell cloning is an excellent way to limit genetic variation, while harnessing phenotypic heterogeneity to establish favorable cell models. Phenotypic heterogeneity of clonally derived cells is often associated with epigenetic variation [41] and triggered by stochastic gene activation events [42], which is an important contributor to reprogramming transitions [43,44]. Systematic studies into stochastic gene expression events have been facilitated by single cell transcriptomics (for recent reviews see [44,45,46]).…”
Section: Discussionmentioning
confidence: 99%
“…Many of the techniques and examples we present may pose a challenge to companies, as new questions arise concerning how the findings could affect a product or program. Given the well-documented plasticity of CHO cells, detailed genetic examination of legacy cell lines runs the risk of generating data that are not easily explained, or even dispute clonality of a cell line that is, in fact, clonal in origin (14)(15)(16)(17). This additional information may contradict the breadth of knowledge that supports a cell line's commercial use, such as extensive characterization, or phenotypic and genotypic stability evaluations.…”
Section: Opinion On Additional Genetic Testingmentioning
confidence: 99%
“…Also, the potential for genetic rearrangements applies and should be considered when designing experiments and interpreting data. However, TLA can be very useful to generate markers for clonality, such as the unique transgene to CHO genomic DNA (TG-CHO) fusions that arise at integration (16). These TG-CHO fusion junctions can be detected by simpler PCR-based methods to follow clonal lineages, as detailed in Section 3.5.…”
Section: Targeted Locus Amplificationmentioning
confidence: 99%